Downstream oil supply chain management: A critical review and future directions. (2nd September 2016) - Lima, Camilo; Relvas, Susana; Barbosa-Póvoa, Ana Paula F.D.
Highlights: We review the works about optimization models applied to downstream oil supply. We analyze the trends and necessities for the downstream segment. We identify the main scientific contributions in the reviewed literature. We find out the major gaps in scientific literature. We established an agenda for future research directions. Abstract: The oil industry has been playing a particular role in the modern economy, acting globally in different countries within competitive business environments. Due to the complexity of the oil supply chain, the associated decision making process is a difficult task, which involves numerous elements from oil supply, going through oil refining, up to oil product distribution. Thus, decision-support tools are often required to assist the decision making in the context of the oil supply chain. The improvement of such decision-support tools is a continuous goal for corporations. From this background, this work aims to review the scientific production about the application of mathematical programming techniques to the distribution problems, faced by diverse entities in the downstream oil supply chain. The main objectives are to point out main contributions, besides identifying the major voids and new trends in order to establish an agenda for future research directions.